Identification and expression analysis of chemosensory genes in the tea green leafhopper, Empoasca onukii Matsuda. (2nd June 2018) - Zhao, Yunhe; Li, Huan; Wang, Qian; Liu, Jingtao; Zhang, Lixia; Mu, Wei; Xu, Yongyu; Zhang, Zhengqun; Gu, Shaohua
Abstract: Tea green leafhopper, Empoasca onukii Matsuda, is one of the major dominant insect pests affecting tea plantations in Asia. Previous studies have demonstrated that E. onukii was significantly attracted by the tea volatiles and repelled by the non‐host plant volatiles. However, the olfactory mechanisms of insect perception of these semiochemicals are still unknown. Odorant‐binding proteins (OBPs) and chemosensory proteins (CSPs) are involved in the initial biochemical recognition steps in semiochemical perception. In this study, a total of 33 OBPs and 24 CSPs were identified in the antennae and body transcriptomes of E. onukii . Among them, 9 OBPs and 17 CSPs were newly identified. Phylogenetic analysis was conducted to compare OBPs and CSPs among Hemiptera insects. Semi‐quantitative RT‐PCR and real‐time quantitative PCR analysis revealed that 24 EonuOBP and 13 EonuCSP genes were mainly or uniquely expressed in the antennae. In addition, one OBP ( EonuOBP49 ) and four CSPs ( EonuCSP4, 7, 12 and 18 ) were more highly expressed in the body than in the antennae. Overall, the present work had provided foundational data to study the physiological roles of the OBPs and CSPs in the tea green leafhopper both in vitro and in vivo.